A case study of the institutional culture at a voluntary-sector counselling center: how does it affect counsellors and their practice?. (1st October 2016) - McDonnell, Mark
ABSTRACT: Person-centered counsellors work in a wide variety of institutional settings, each with their own group cultures. This case study examines the group culture among counsellors working at a voluntary-sector-independent counselling center and seeks to determine how this culture affected counsellors' sense of themselves and the way they were with their clients. A grounded theory methodology was employed. Data were collected through sentence completion exercises facilitated in small groups and through individual responses to questions about the impact of institutional culture on the work with clients, which elicited open-ended pieces of reflexive writing. In this particular Center, counsellors felt valued and a sense of belonging. Belonging was so important to participants that they would submit, at times, to what they felt were unnecessary group policies, in order to remain connected to the group. Counsellors perceived the culture at the Center as positively affecting their way of being with clients. Some compared it with less positive experiences in public sector settings. The findings are seen as supportive of theory relating to the actualizing process and social mediation.